Treatment of facial acne scar using Fractional Er: YAG laser - toama, Ali S.; Saleh, Wasan M.; Kadhem, Ali Abdul J. (Iraqi Journal of Laser, 2020)
Background: Acne is a common disorder experienced by adolescents and persists into adulthood in approximately 12%–14% of cases with psychological and social implications of high gravity. Fractional resurfacing employs a unique mechanism of action that repairs a fraction of skin at a time. The untreated healthy skin remains intact and actually aids the repair process, promoting rapid healing with only a day or two of downtime. Aims: This study, was designed to evaluate the safety and effectiveness of fractional photothermolysis (fractionated Er: YAG laser 2940nm) in treating atrophic acne scars. Methods: 7 females and 3 males with moderate to severe atrophic acne scarring were enrolled in this study that attained private clinic for Dermatology and Laser in Baqubah city of Diyala - Iraq during the period from 1st of June 2019 to 10th of October 2019. Fractional Er:YAG laser 2940 nm wavelength was delivered to the whole face with a single pass treatment and for the acne scar areas with two passes. Therapeutic outcomes were assessed by standardized digital photography. Results: Three patients (30%) reported excellent improvement, five patients (50%) significant improvement, one patient (10%) moderate improvement, and one patient (10%) mild improvement in the appearance of the acne scars. Conclusion: Fractional Er: YAG a safe and effective option for the treatment of acne scars in Iraqi patients by offering faster recovery time with no or mild side effects in comparison to other traditional modalities.